Arthroscopic anterior cruciate ligament reconstruction in a patient with multiple hereditary exostoses - Zmerly, Hassan; Akkawi, Ibrahim; Libri, Rolando; Moscato, Manuela; Di Gregori, Valentina (Acta Biomedica Atenei Parmensis, 2021)
Background Multiple hereditary exostoses (MHE) also known as Multiple Osteochondromas is a rare benign bone tumour disease, characterized by multiple osteocartilaginous masses. The knee is one of the most affected sites. Anterior cruciate ligament (ACL) surgery is the most common and generally most successful surgical knee procedure; however, the association between MHE and ACL reconstruction is very rare and may represent a challenging procedure because of the anatomical anomaly related to presence of multiple masses around the knee. Here, we present a case report of ACL reconstruction in a patient affected by multiple exostoses. Case report The patient was a 30-year-old woman affected by MHE, with an ACL tear arising after knee trauma. As the patient complained of pain, swelling and the knee “giving way”, she successfully underwent arthroscopic-assisted ACL reconstruction using quadrupled hamstring tendon grafts, with femoral suspension and double tibial fixations. Conclusion Symptomatic ACL tears in a patient affected by MHE should be considered for arthroscopic reconstruction, which requires that particular attention be paid to tendons harvesting, tunnel placement and the choice of graft fixation system, given the presence of multiple masses around the knee